Designing Library Instruction for Students with Learning Disabilities - Willis, Carolyn; Nall, H. Clark; Hoover, Jeanne K. (My University, 2013)
East Carolina University is the home of an innovative program for students with learning disabilities, Project STEPP. Librarians at ECU’s Joyner Library have collaborated with Project STEPP since 2010 to provide library instruction for the program’s students. In the course of our collaboration, we have considered principles of Universal Design for Learning and the special needs of students with learning disabilities in library instruction. In this paper, we discuss our collaboration with the program, our classroom experience and assessment with the students, and future plans for improving instruction.
Keywords: Academic libraries; Library instruction; Information literacy instruction; Project STEPP; Learning disabilities